MEMILIH FIGUR PUBLIK BERKESADARAN GENDER: STUDI JARINGAN PENGGUNAAN TOKOH SELEBRITI UNTUK TEMA ‘SETARA’ PADA AKUN INSTAGRAM KEMENPPPA - Angeliqa, Fitria; Said, Martriana Ponimin (Master of Communication Science Program, Universitas Diponegoro, 2020)
The government had used convergence media to disseminate policies to obtain useful feedback. The purpose of this study searched the implications of the communication technology in the participation of social media users, Instagram, in its debate with public policies related to the issue of women's equality promoted by the Ministry of PPPA. The results became an evaluation of the institutions in determining the use of celebrities who have a vast network of friends. The issue of government policy did not get an adequate response because of the lack of audience knowledge and their reflection on the topic—and vice versa. This study used the concept of the communication network with a constructivist paradigm. The unit of analysis is text, posting by selected public figures on the 'Setara' issue in the Kemenpppa account. The collecting data technique used a mix-method to obtain completeness—the data analysis technique used quantitative network analysis with UCI-Net and discourse analysis for qualitative. The results showed that public figures could not be sub-groups/betweenness centrality that gaining public participation. The inaccuracy in choosing celebrity figures for disseminating gender awareness caused equality issues, not fulfilling expectations, from secondary data spread of the gender issues to the weak content interaction.